2006
DOI: 10.1002/jbm.a.30749
|View full text |Cite
|
Sign up to set email alerts
|

Biological performance of a new β‐TCP/PLLA composite material for applications in spine surgery: In vitro and in vivo studies

Abstract: The objective of this research was to carry out an in vitro and in vivo study of the biological performance of PLLA/beta-TCP composite materials, to estimate the scope of their potential applications in bone surgery. Samples with increasing beta-TCP (0-60% w/w) contents were processed by injection molding. The in vitro study consisted of an evaluation of inflammatory potential by assaying the IL-1alpha secreted by monocytes, and then cell proliferation (counting) and phenotype expression (PAL and I collagen) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 40 publications
(24 reference statements)
2
49
0
Order By: Relevance
“…The initial fibrous tissue formation observed in this study has been previously reported with PLA implants inserted into rabbits [20]. However, this fibrous tissue does not always disappear and may be present after more than 6 months [20,23,24]. The absence of fibrous tissue at 12 months in our study may be related to the presence of the b-TCP particles, as b-TCP has been shown to decrease the inflammatory reaction when composite PLA/b-TCP scaffolds were implanted [20].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The initial fibrous tissue formation observed in this study has been previously reported with PLA implants inserted into rabbits [20]. However, this fibrous tissue does not always disappear and may be present after more than 6 months [20,23,24]. The absence of fibrous tissue at 12 months in our study may be related to the presence of the b-TCP particles, as b-TCP has been shown to decrease the inflammatory reaction when composite PLA/b-TCP scaffolds were implanted [20].…”
Section: Discussionsupporting
confidence: 78%
“…It is the accumulation of this acid which becomes toxic [22]. The initial fibrous tissue formation observed in this study has been previously reported with PLA implants inserted into rabbits [20]. However, this fibrous tissue does not always disappear and may be present after more than 6 months [20,23,24].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The addition to beta-TCP particles of a plastic material, such as resorbable lactic acid polymer (PLLA), increases breaking strength and provides real capacity to withstand plastic and elastic strain [1]. Such composite materials can retain high strength over time.…”
Section: Introductionmentioning
confidence: 99%